Teaching Narrative Text in Junior High School: Digital Story Telling in English as a Foreign Language (EFL) Context - Mutiara Shasqia (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
Current learning perspective is a process of giving learners to have the ability or skills in an innovative learning situation. In learning English, it requires techniques and creative so that learners have competence in writing narrative text. This research aims at proving digital storytelling can improve the junior high school students’ writing skill in making narrative text. Digital storytelling is one of the media for teaching writing narrative text. The objectives of this qualitative study are to discuss the technique of teaching digital storytelling in writing process based on the selected literature and current study regarding the use of digital storytelling. This ongoing research tries to give an additional perspective and motivation to improve students’ writing skill in the narrative text through digital storytelling. This study reveals that by using digital storytelling, the students can mastery some aspect in English.